Chlorination decomposition of struvite and recycling of its product for the removal of ammonium-nitrogen from landfill leachate. (October 2015) - Huang, Haiming; Huang, Lingyun; Zhang, Qingrui; Jiang, Yang; Ding, Li
Graphical abstract: Highlights: The chlorination decomposition of struvite was performed in this study. 98% of NH4 -N in struvite was removed at pH 6 and Cl/NH4 -N wt ratio of 8.2:1. 92% of NH4 -N in landfill leachate could be removed at a precipitation pH of 9. Struvite chlorination decomposition product could be effectively recycled. Abstract: Struvite (MgNH4 PO4  ⋅ 6H2 O) precipitation is a promising method for ammonium (NH4 + ) removal from the wastewater. However, the high cost incurred with the use of magnesium and phosphate sources hinders the successful application of this method. This paper presents a novel recycling technology of struvite that is based on the chlorination decomposition of struvite. The study results indicated that struvite can be effectively decomposed by sodium hypochlorite and that the solid/liquid ratio of struvite in solution did not affect the ammonium-nitrogen (NH4 -N) decomposition efficiency of struvite. Through the analysis of the reaction process, the mechanism of struvite decomposition was proposed to be simultaneous dissolution and oxidation of struvite, and the main component of the decomposition product generated was determined to be newberyite, dissolved HPO4 2− and Mg 2+, and magnesium phosphate. When the decomposition product was recycled, its pH had to be adjusted for high NH4 -N removal. NH4 -N of 92% could be removed from landfill leachate when the decomposition product solution pH before recycling was adjusted to 3 and the precipitation pH was maintained at 9. A five-cycle recycling process showed that recycling of struvite chlorination decomposition product was a highly efficient and sustainable method for the removal of NH4 -N. An economic evaluation showed that the use of recycled struvite for the five-process cycles by the proposed process could save the cost of chemicals by approximately 34% as compared to the use of pure chemicals.